2014
DOI: 10.7566/jpsj.83.093705
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Transition Temperatures of up to 47 K from Simultaneous Rare-Earth Element and Antimony Doping of 112-Type CaFeAs2

Abstract: The effects of simultaneous Sb doping on the superconductivity of 112-type Ca 1¹x RE x FeAs 2 (RE = La, Ce, Pr, and Nd) were studied through measurements of the magnetization and electrical resistivity. In Sb-free materials, the superconducting transition temperature T c of the La-doped sample was 35 K, while those of the Pr-and Nd-doped samples were ³10 K; no superconductivity was observed in the Ce-doped sample. Sb doping increased the T c of all REdoped samples: T c increased to 47, 43, 43, and 43 K for RE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 28 publications
0
79
0
Order By: Relevance
“…Furthermore, Co-co-doped (Ca,La)112 showed large diamagnetic screening below T c , suggesting bulk superconductivity. At present the reason for relatively high T c by direct doping to Fe site is unclear, but EDX analysis showed that La composition in (Ca,La)112 decreased in Co-co-doped (Ca,La)112, similar to decrease of La composition in Sb-co-doped (Ca,La)112 [13] . Optimization of As-Fe-As bond angle might be another reason of improvement of superconducting properties as observed in Sb-co-doped samples [13] .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, Co-co-doped (Ca,La)112 showed large diamagnetic screening below T c , suggesting bulk superconductivity. At present the reason for relatively high T c by direct doping to Fe site is unclear, but EDX analysis showed that La composition in (Ca,La)112 decreased in Co-co-doped (Ca,La)112, similar to decrease of La composition in Sb-co-doped (Ca,La)112 [13] . Optimization of As-Fe-As bond angle might be another reason of improvement of superconducting properties as observed in Sb-co-doped samples [13] .…”
Section: Resultsmentioning
confidence: 97%
“…(Ca,RE)112 compounds have monoclinic crystal structure with space group P2 1 [9] or P2 1 /m [10] . In our previous study, the high pressure synthesis was found to be an effective way to [13] . Sb-co-doping increases b-axis length accompanying improvement of As-Fe-As bond angle.…”
Section: Introductionmentioning
confidence: 98%
“…As plotted in Fig. 4 47 and the hole doped 122 compound BaK122(T c =38K) 48 are always characterized by h P n = 1.35 ∼ 1.4Å and the bond angle of P n-Fe-P n α ∼ 109. 61 , and so on.…”
mentioning
confidence: 93%
“…Recently, novel 112-type iron-based superconductors have received considerable attention [1][2][3] because the superconductivity induced by the simultaneous doping 4 of rare earth (RE) elements and antimony results in superconducting transition temperatures up to 47 K. 5,6 The chemical formula of these 112-type iron-based materials is written as Ca 1−x RE x FeAs 2 (RE = La, Ce, Pr, Nd, Sm, Eu, Gd) [1][2][3] because the partial substitution of RE for Ca is necessary to stabilize the 112 phase. [1][2][3] These materials crystalize in a monoclinic structure with space group P2 1 (No.…”
mentioning
confidence: 99%